Gambaran Kualitas Tidur Para Penderita Hipertensi Lansia di Wilayah Kota Banjarmasin - Ermeisi Er Unja; Gertrudis Tutpai; Anastasia Maratning (Institute of Advanced Knowledge and Science, 2024)
Hypertension is currently still the number one non-communicable disease in Banjarmasin. Hypertension caused many problems in physical, psychological, social and even the most serious impact in the form of death. The main complaint of people with hypertension is poor sleep quality, which can cause memory impairment, cognitive abilities and decreased health. To determine the picture of sleep quality in patients with hypertension in Banjarmasin. This study is a descriptive quantitative research that was conducted at some area in Banjarmasin. There are totaling 120 elderly patients with hypertension be a respondents that taken by random Sampling. The research instrument used the Pittsburgh Sleep Quality Index (PSQI) questionnaire, the analysis of research data used univariate analysis, namely frequency distribution. Sleep quality in hypertensive patients in the work area of the Pekauman Health Center in 2023 obtained the results of respondents who had poor sleep quality as many as 98 respondents (81,6%) and 22 respondents (18,4%) had good sleep quality. The sleep quality of elderly people with hypertension in some area in Banjarmasin has a poor sleep quality, which is 81,6% in 98 respondents in the study. The importance of the role of nurses to provide education to improve sleep quality.